Sickle Cell Disease in Africa: SickleInAfrica Registry in Ghana, Nigeria and Tanzania - Jack Morrice; Wilson Mupfururirwa; Reuben I. Chianumba; Evans Xorse Amuzu; Daniel Kandonga; Victoria Nembaware; Mario Jonas; Jade Hotchkiss; Upendo Masamu; Arthemon Nguweneza; Bruno P. Mmbando; Irene Minja; et al. (eJHaem)
ABSTRACT Introduction Sickle cell disease (SCD) is most prevalent in Sub‐Saharan Africa (SSA), where incomplete patient profiles and limited management strategies hinder research and healthcare standards. Methods We describe the first large‐scale and multinational assessment of 13,403 SCD patients enrolled from 2017–2021 across 31 facilities in Ghana, Nigeria, and Tanzania into the SickleInAfrica consortium registry. We used hierarchical regression models to estimate and analyze the demographics, adoption levels of SCD diagnosis and therapies. Results The average age at diagnosis was 3 months, 19 months and 3 years in Ghana, Nigeria and Tanzania respectively, reflecting differences in country‐specific newborn screening programs and policies. Hydroxyurea (HU) use was highest in Ghana (21%), followed by Nigeria (12%) and Tanzania (6%), with significant variability across facilities. Sex differences in SCD management were observed, with males more likely to receive HU and blood transfusions. At the consortium level, HU initiation correlated with enrolment age rather than age at diagnosis, highlighting the need for earlier intervention. Conclusions Our findings highlight the potential of the SickleInAfrica registry toward enhancing understanding of regional disparities in SCD care and potential gender inequalities, emphasizing the need for enabling policies toward strengthened SCD research and improved quality of life and care of patients in Africa.